Recreational land use: issues of development and assessement of potential - Tretiak, V.; Marchenkova Т. (Land Management, Cadastre and Land Monitoring, 2020)
The article is researched and constructed on the basis of the use of general scientific and special methods of scientific cognition, which yielded valuable results. Key theoretical developments of the article are based on modern achievements, provisions and postulates of the environmental economics, applied research of the world and national level on the study of the recreational land use. The research was carried out on the basis of statistical and analytical data of the Ministry of Environmental Protection, State Geocadastre of Ukraine, State Committee of Statistics of Ukraine, Ministry of Economy of Ukraine, materials of scientific-practical conferences, symposia, seminars, author’s own calculations. The assessment of recreational land is central to the natural and recreational potential of the area under investigation. They cover primarily geological and geomorphological recreation resources, climatic conditions, vegetation, water and land recreation resources, recreational resources of wildlife, and resources of educational tourism. The functional model of the cadastral valuation of the value of potentially suitable lands for recreation is developed and the scheme of the methodological process of cadastral valuation of the recreational potential of land and other natural resources is substantiated. The most important problems of recreational land use in Ukraine are ensuring a high quality of recreation, expanding the possibilities to use recreational land and resources that are closely linked to it, meeting the needs of people for communion with wildlife and recovering public health. However, the radical transformation of landscapes and the large-scale urbanization have led to a decrease in the recreational value of landscapes and thus to the formation of recreational zones on land of little use for other economic purposes. All of this has a negative impact on the quality of recreation, the variety of recreational activities and the ability to stay in the recreational sphere of landscapes that meet the need of the population for rest. Key words. Recreational land use, natural resource potential, recreational potential, cadastral valuation, functional use of recreation land.